Auditoría De Gestión A La Demarcación Hidrográfica Puyango-Catamayo De La Secretaría Nacional Del Agua (Senagua Zona 7), Periodo Comprendido Del 01 De Enero Al 31 De Diciembre Del 2012 - Cevallos Bravo, Karina Natali (2016)
This work was prepared based on the General Objective perform management “AUDIT THE RIVER BASIN DISTRICT PUYANGO-CATAMAYO NATIONAL SECRETARIAT OF WATER (SENAGUA ZONE 7) PERIOD FROM 01 JANUARY TO 31 DECEMBER 2012”, where it was applied each stage of the process to assess Auditing Internal Control, to determine compliance with laws, apply performance indicators to measure the effectiveness and efficiency and provide the report to the Coordinating Institution. The methodology used for the implementation of the Performance Audit is: a previous visit to Puyango-Catamayo River Basin, where interviews with officials of the areas evaluated were performed allowing to obtain information relevant to program development was performed work and internal control questionnaires to assess and evaluate the findings, in which we rely for comment, conclusions and recommendations. In the Performance Audit on the River Basin Puyango-Catamayo in the period of its work during 2012, the results show that there have been no audits of management above, plus there have been some deficiencies in contravention to the provisions of the rules Internal Control, as the demarcation is not rotated and the same staff are not accountable for the achievement of objectives and results obtained in this way to reduce the risk of errors, administrative shortcomings and misuse of resources and thus comply with the objectives for institutional improvement, also does not have sufficient financial information to support the activities . Based on the evaluation of internal control system concluded that the level of trust and risk is moderate so compliance is testing and substantive testing was applied.